60.3k views
4 votes
Show that cos(3x) = cos3(x) − 3 sin2(x)cos(x). (Hint: Use cos(2x) = cos2(x) − sin2(x) and the cosine sum

formula.)

User Ahx
by
5.6k points

1 Answer

7 votes

Explanation:

To prove:


\cos 3x=\cos^3x-3\sin^2 x\cos x

Identities used:


\cos(A+B)=\cos A\cos B+\sin A\sin B ......(1)


\sin 2A=2\sin A\cos A ........(2)


\cos 2A=\cos^2A-\sin^2 A .......(3)

Taking the LHS:


\Rightarrow \cos 3x=\cos (x+2x)

Using identity 1:


\Rightarrow \cos (x+2x)=\cos x\cos 2x-\sin x\sin 2x

Using identities 2 and 3:


\Rightarrow \cos x(\cos ^2x-\sin^2 x)-\sin x(2\sin x\cos x)\\\\\Rightarrow \cos^3x-\sin^2x\cos x-2\sin^2 x\cos x\\\\\Rightarrow \cos^3x-3\sin^2x\cos x

As, LHS = RHS

Hence proved

User Maxime P
by
5.4k points